Conceptualisation and Validating Benefidonors Model in Waqf - Fauzias Mat Nor; Fuadah Johari; Dato' Hasnah Hj Haron; Zurina Shafii; Syahidawati Hj. Shahwan; Hanim Hj Misbah; Amir Shaharuddin; Azuan Ahmad; Nur Atika Atan; Muhammad Mohamad Yusoff (USIM Press, 2024)
Vol. 19, No. 1 Page (106-119)